Hubungan Kejadian Kekurangan Energi Kronis dengan Kejadian Anemia pada Ibu Hamil Trimester I - Ekawati, Ni Putu; Mahayati, Ni Made Dwi; Tirtawati, Gusti Ayu (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
The prevalence of anemia in pregnancy globally reaches 38.8% or 32 million pregnant women. One cause of anemia in pregnant women is nutritional status which can be measured using the Upper Arm Circumference (LILA). This study aims to determine the relationship between chronic energy deficiency (CED) and the incidence of anemia in pregnant women in the first trimester in the Working Area of Puskesmas II Negara. Researchers used a quantitative analytical survey approach with a cross-sectional approach. Sampling involved 42 pregnant women. Researchers measured LiLa and Hb levels and recorded them in a data collection format. Data analysis was carried out using univariate and bivariate methods, with the Spearman rank test. The results showed that CED is associated with the incidence of anemia in pregnant women in the first trimester with a p-value of 0.02 (<0.05), r = 0.469 which indicates a positive direction in the same direction between variables, meaning that in this study when the LiLa size is smaller, the lower the Hb levels in pregnant women. A high r value (rho) of 0.469 indicates a moderate correlation between KEK and the incidence of anemia in pregnant women in the first trimester in the working area of the Negara II Public Health Center. Young women, women of childbearing age, or prospective pregnant women are expected to pay more attention to nutritional intake to prevent chronic energy deficiency, which can increase the risk of anemia during pregnancy.